2016
DOI: 10.1155/2016/1279051
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic and Intrinsic Regulation of Axon Regeneration by MicroRNAs after Spinal Cord Injury

Abstract: Spinal cord injury is a devastating disease which disrupts the connections between the brain and spinal cord, often resulting in the loss of sensory and motor function below the lesion site. Most injured neurons fail to regenerate in the central nervous system after injury. Multiple intrinsic and extrinsic factors contribute to the general failure of axonal regeneration after injury. MicroRNAs can modulate multiple genes' expression and are tightly controlled during nerve development or the injury process. Evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 115 publications
1
22
0
Order By: Relevance
“…Data were compared by one-way or two-way ANOVA. *p < 0.05 vs sham group or NC mimic versatile functions in key events such as oligodendrocyte development, axonal regeneration, and remyelination [7,26]. In the present research, we validated the potent functions of miR-29a/199B in neurologic and locomotor functional recovery in a rat model with the involvement of downregulation of RGMA and the suppression of the STAT3 signaling pathway.…”
Section: Discussionsupporting
confidence: 58%
“…Data were compared by one-way or two-way ANOVA. *p < 0.05 vs sham group or NC mimic versatile functions in key events such as oligodendrocyte development, axonal regeneration, and remyelination [7,26]. In the present research, we validated the potent functions of miR-29a/199B in neurologic and locomotor functional recovery in a rat model with the involvement of downregulation of RGMA and the suppression of the STAT3 signaling pathway.…”
Section: Discussionsupporting
confidence: 58%
“…MiRNAs are present in all kinds of systems, including the central nervous system, and their dysregulation was related to the multiple neurotraumatic diseases (4). Recently, the role of the miRNAs in SCI development and their value in SCI diagnosis were reported in several papers (5)(6)(7). The microarray analysis revealed that miR-138 expression was signifi cantly enriched in the adult rat spinal cord following SCI (8).…”
Section: Introductionmentioning
confidence: 99%
“…In spinal cord injury (SCI), changes in exosomal miRNAs reflect many of the barriers to CNS regeneration. For example, SCI can differentially regulate exosomal miRNAs that modulate calcium signaling, synaptic function, axon guidance [ 11 – 13 ], axon degeneration, inhibitory molecule expression, and scar tissue formation [ 14 ], suggesting engineered EV combinations may be useful in counteracting or modulating the signaling pathways underlying the default healing response in the CNS. Though EV biology in the visual system is less developed, a number of recent studies indicate EVs, like exosomes and microvesicles, and their cargoes, particularly miRNAs and inflammatory proteins, may be used to detect, monitor, and prognosticate retinal and possibly optic nerve trauma and disease.…”
Section: Evs As Biomarkers In the Visual Systemmentioning
confidence: 99%